Validation of success factors for dance community sites: towards a model for predicting appreciation of online community websites. (28th June 2007) - Ten Thij, E.; Van De Wijngaert, L.
In the Netherlands, dance music and dance parties are rather popular. From the beginning, dance fans have been involved with the internet. Many dance websites are developing from content-oriented websites into real community sites and there is a need for information on how to support and empower these sites. Although we find guidelines and design principles for successfully developing and maintaining online communities in the literature, these guidelines and design principles are based more on experience and research on offline communities than on empirical verification (Leimeister et al., 2004). We sorted the guidelines and design principles into categories of website features, and asked ten online dance communities via an online questionnaire to rate the individual features and the dance community sites they were familiar with from the selected sample. With a few exceptions, our categories were confirmed. Correlation analysis showed that there are significant relationships between the appreciation of features and websites.